Analogy between agronomic and grain quality attributes of wheat for response to crop seasons, locations, site-year and genotype- environment interactions - Mohan, Devinder; Singh, Anju Mahendru; Ahlawat, Arvind; Gupta, Raj Kumar (Journal of Cereal Research, 2014)
Locations, crop years and their interactions for yield and quality determinants were compared by evaluating 14 wheat genotypes for four crop seasons across six diverse locations in India. A signifcant impact of locations, crop seasons and location-year interactions was noted for fve important agronomic and grain quality parameters. Sites and crop seasons were equally relevant for grain quality but in agronomic traits, sites contributed more to phenotypic expressions like plant height and days to heading. Genotype-environment interactions were rare as only genotype-location for sedimentation volume and genotype-year for grain hardness index were prominent but many genotypes could thwart such interactions, too. For all agronomic traits except kernel weight, locations expressed more variability than the genotypes. It is suggested that agronomic expression at a test site cannot be rated for any refection of grain properties but a crop season unfavorable for yield often has less desired quality attributes.